The effect of major depressive disorder comorbidity on ischemia-modified albumin levels, a marker of oxidative stress, and antioxidant defense system in patients with obsessive compulsive disorder - Zengil, Sertaç; Laloğlu, Esra (Frontiers in Psychiatry, 2024)
Objective The aim of this study was to examine the levels of oxidant and antioxidant markers in patients with obsessive-compulsive disorder (OCD) and to investigate whether these levels change in the presence of major depressive disorder (MDD) comorbidity. Methods This study was completed with 23 OCD patients with MDD comorbidity (OCD+MDD), 21 OCD patients without MDD comorbidity (OCD-MDD) and 21 healthy controls. Oxidative stress levels of the cases’ were determined by ischemia modified albumin (IMA) and malondialdehyde (MDA) measurements and antioxidant levels were determined by superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) measurements. One-way analysis of variance (ANOVA) and unpaired Student’s t-test were used to compare the study groups. Post hoc Bonferroni test was used for the degree of significance between groups, and repeated measures analysis of covariance (ANCOVA) was used to investigate the effect of age and gender. Results IMA and MDA levels were significantly higher in the OCD group compared to the control group, and SOD, CAT and GSH-Px levels were lower in the OCD group compared to the control group (p<0.01). IMA levels were significantly higher in the OCD+MDD group compared to the OCD-MDD group, while SOD, CAT and GSH-Px levels were significantly lower in the OCD+MDD group compared to the OCD-MDD group (p<0101). MDA levels were significantly higher in the OCD+MDD group compared to the OCD-MDD group (p=0.009). When the entire OCD patient group was examined, significant, powerful, positive correlations were observed between Y-BOCS and HDRS scores and IMA and MDA, and significant powerful negative correlations between Y-BOCS and HDRS scores and SOD, CAT, and GSH-Px (p<0.001 for all). In OCD+MDD group, oxidative stress markers increased significantly in parallel with the severity of depression, while antioxidant levels decreased (p=0.003 for IMA, p<0.001 for others). Conclusions We believe that parameters indicating impaired oxidant/antioxidant balance in patients with obsessive-compulsive disorder may help to elucidate the cause of the disease and may be potentially useful biomarkers in the diagnosis and determination of the severity of comorbid MDD.